Altitude and Erythropoietin: Comparative Evaluation of Their Impact on Key Parameters of the Athlete Biological Passport: A Review - Saugy, Jonas J.; Schmoutz, Tania; Botrè, Francesco (Frontiers in Sports and Active Living, 2022)
The hematological module of the Athlete's Biological Passport (ABP) identifies doping methods and/or substances used to increase the blood's capacity to transport or deliver oxygen to the tissues. Recombinant human erythropoietin (rhEPOs) are doping substances known to boost the production of red blood cells and might have an effect on the blood biomarkers of the ABP. However, hypoxic exposure influences these biomarkers similarly to rhEPOs. This analogous impact complicates the ABP profiles' interpretation by antidoping experts. The present study aimed to collect and identify, through a literature search, the physiological effects on ABP blood biomarkers induced by these external factors. A total of 43 studies were selected for this review. A positive correlation (R2 = 0.605, r = 0.778, p < 0.001) was identified between the hypoxic dose and the increase in hemoglobin concentration (HGB) percentage. In addition, the change in the reticulocyte percentage (RET%) has been identified as one of the most sensitive parameters to rhEPO use. The mean effects of rhEPO on blood parameters were greater than those induced by hypoxic exposure (1.7 times higher for HGB and RET% and 4 times higher for hemoglobin mass). However, rhEPO micro-doses have shown effects that are hardly distinguishable from those identified after hypoxic exposure. The results of the literature search allowed to identify temporal and quantitative evolution of blood parameters in connection with different hypoxic exposure doses, as well as different rhEPOs doses. This might be considered to provide justified and well-documented interpretations of physiological changes in blood parameters of the Athlete Biological Passport.